Circ_0007535 upregulates TGFBR1 to promote pulmonary fibrosis in TGF-β1-treated lung fibroblasts via sequestering miR-18a-5p - Shen, Ming; Wang, Xinyi; Chang, Xiaofeng; Li, Zhun; Jiang, Na; Han, Zhuoyue; Liu, Xin (Autoimmunity (Chur, Switzerland), 2023)
Circular RNAs (circRNAs) are functional molecules in all kinds of fibrosis diseases. The current study was performed for the exploration of circ_0007535 in pulmonary fibrosis. RNA levels for circ_0007535, miR-18a-5p, and transforming growth factor-β receptor 1 (TGFBR1) were assayed via a reverse transcription-quantitative polymerase chain reaction. Cell growth was determined by cell counting kit-8 assay for viability and ethynyl-2'-deoxyuridine assay for proliferation. Cell invasion and migration were examined by transwell assay and scratch assay. Western blot was performed for the detection of different proteins. Enzyme-linked immunosorbent assay was used to assess inflammatory response. The interaction analysis was conducted using dual-luciferase reporter assay, RNA immunoprecipitation assay, and biotin-coupled pull-down assay. Circ_0007535 was significantly upregulated by TGF-β1 in HFL1 cells. TGF-β1-induced proliferation, motility, ECM accumulation, and inflammatory reaction in HFL1 cells were alleviated by circ_0007535 knockdown. Circ_0007535 exhibited interaction with miR-18a-5p, and miR-18a-5p inhibition reversed all influences of circ_0007535 downregulation in TGF-β1-treated HFL1 cells. Circ_0007535 acted as a miR-18a-5p sponge to regulate the expression of downstream target TGFBR1. MiR-18a-5p induced TGFBR1 level inhibition to attenuate TGF-β1-mediated cell injury in HFL1 cells. This study evidenced that circ_0007535 facilitated TGF-β1-induced pulmonary fibrosis by depending on the absorption of miR-18a-5p to upregulate TGFBR1.Circular RNAs (circRNAs) are functional molecules in all kinds of fibrosis diseases. The current study was performed for the exploration of circ_0007535 in pulmonary fibrosis. RNA levels for circ_0007535, miR-18a-5p, and transforming growth factor-β receptor 1 (TGFBR1) were assayed via a reverse transcription-quantitative polymerase chain reaction. Cell growth was determined by cell counting kit-8 assay for viability and ethynyl-2'-deoxyuridine assay for proliferation. Cell invasion and migration were examined by transwell assay and scratch assay. Western blot was performed for the detection of different proteins. Enzyme-linked immunosorbent assay was used to assess inflammatory response. The interaction analysis was conducted using dual-luciferase reporter assay, RNA immunoprecipitation assay, and biotin-coupled pull-down assay. Circ_0007535 was significantly upregulated by TGF-β1 in HFL1 cells. TGF-β1-induced proliferation, motility, ECM accumulation, and inflammatory reaction in HFL1 cells were alleviated by circ_0007535 knockdown. Circ_0007535 exhibited interaction with miR-18a-5p, and miR-18a-5p inhibition reversed all influences of circ_0007535 downregulation in TGF-β1-treated HFL1 cells. Circ_0007535 acted as a miR-18a-5p sponge to regulate the expression of downstream target TGFBR1. MiR-18a-5p induced TGFBR1 level inhibition to attenuate TGF-β1-mediated cell injury in HFL1 cells. This study evidenced that circ_0007535 facilitated TGF-β1-induced pulmonary fibrosis by depending on the absorption of miR-18a-5p to upregulate TGFBR1.